Pathways between neurocognition, social cognition and emotion regulation in bipolar disorder. (20th May 2014) - Van Rheenen, T. E.; Meyer, D.; Rossell, S. L.
<x xml:space="preserve">Abstract</x> Objective Converging evidence suggests that in bipolar disorder (BD), social cognition and emotion regulation are affected by the capacity for effective neurocognitive function. Adaptive emotion regulation may also rely on intact social cognition, and it is possible that social cognition acts as a mediator in its relationship with neurocognition. We aimed to address this hypothesis by explicitly examining interrelationships among neurocognition, social cognition and emotion regulation in an out‐patient sample meeting criteria for a DSM‐IV‐TR diagnosis of BD compared with controls. Method Fifty‐one BD patients and 52 healthy controls completed a battery of tests assessing neurocognition, social cognition (emotion perception and theory of mind) and emotion regulation. Results Path analysis revealed that in BD, neurocognition was associated with social cognition, but social cognition was not associated with emotion regulation as expected. In contrast, a component of social cognition was found to mediate the relationship between neurocognition and emotion regulation in healthy controls. Conclusion These findings highlight differences in the pattern of associations between neurocognition, social cognition and emotion regulation across BD patients and controls. In the present data, these results appear to indicate that neurocognitive and social cognitive abilities generally operate in isolation from emotion regulation in BD.